Introduction to partial differential equations - Olver, Peter J. (New York Springer, 2014)
This textbook is designed for a one year course covering the fundamentals of partial differential equations, geared towards advanced undergraduates and beginning graduate students in mathematics, science, engineering, and elsewhere. The exposition carefully balances solution techniques, mathematical rigor, and significant applications, all illustrated by numerous examples. Extensive exercise sets appear at the end
Keywords: Models, Theoretical; Partial Differential Equations